IL-8 Gene Variants are Associated with Lung Function Decline and Multidimensional BODE Index in COPD Patients But Not with Disease Susceptibility: A Validation Study. (1st February 2015) - Córdoba-Lanús, Elizabeth; Baz-Dávila, Rebeca; Espinoza-Jiménez, Adriana; Rodríguez-Pérez, María C.; Varo, Nerea; de-Torres, Juan P.; González-Almeida, Delia; Aguirre-Jaime, Armando; Casanova, Ciro
Abstract Background and objective: COPD is a leading cause of dead worldwide and tobacco smoking is its major risk factor. IL8 is a proinflammatory chemokine mainly involved in the acute inflammatory reaction. The aim of this study was to test the association of IL-8, CXCR1 and CXCR2 gene variants and COPD susceptibility as part of a replication study and explore the effect of these variations in disease progression. Methods: 9 tagSNPs were genotyped in 728 Caucasian individuals (196 COPD patients, 80 smokers and 452 non-smoking controls). Pulmonary compromise was evaluated using spirometry and clinical parameters at baseline and annually over a 2 years period. We also determined plasma levels of TNF-α, IL-6, IL-8 and IL-16 in COPD patients. Results: There was a lack of association between gene variants or haplotypes with predisposition to COPD. No correlation was observed between the polymorphisms and cytokines levels. Interestingly, significant associations were found between carriers of the rs4073A (OR = 3.53, CI 1.34-9.35, p = 0.01), rs2227306C (OR = 5.65, CI 1.75–18.88, p = 0.004) and rs2227307T (OR = 4.52, CI = 1.49–12.82, p = 0.007) alleles in the IL-8 gene and patients who scored higher in the BODE index and showed an important decrease in their FEV1 and FVC during the 2 years follow-up period (p < 0.05). Conclusions: Despite no association was found between the studied genes and COPD susceptibility, three polymorphisms in the IL-8 gene appear to be involved in a worse progression of the disease, with an affectation beyond the pulmonary function and importantly, a reduction in lung function along the follow-up years.